April D. DeConick, The Gnostic New Age: How a Countercultural Spirituality Revolutionized Religion from Antiquity to Today - Huff, Peter A. (The pomegranate, 2022)
April D. DeConick, The Gnostic New Age: How a Countercultural Spirituality Revolutionized Religion from Antiquity to Today (New York: Columbia University Press, 2016), 380 pp., $37.00 (cloth), $28.00 (paperback).